Elemene industrialized production automatic receiving control method - LIU LIMIN; YU YUAN; YANG YOUJIAN; JIAN WEIGUANG (2016)
The invention relates to the technical field of drug production, and particularly relates to an elemene industrialized production automatic receiving control method. The method comprises the following steps: (1) zedoary oil is taken to be placed in a raw material kettle, and a fractionation device is used for vacuum precise fractionation; (2) a near infrared probe on an extraction device is used for monitoring information of each fraction parameter; (3) a near infrared spectrometer transmits monitored parameter information to an online monitoring and analysis system, whether each fraction contains the elemene is judged, and the analysis result is transmitted to a control center; and (4) the control center sends an instruction to an automatic control valve for regulation. The existing elemene industrialized production mode is broken, the near infrared probe, the vacuum precise fractionation device and the online detection analysis system are delicately matched and used, the elemene industrialized production au